Bioremediation of hexamine and formaldehyde using a radio-tolerant bacterial consortium for efficient pollutant and COD removal - Ahmed, S. K. Wasim; Ray Chaudhuri, Shaon (Frontiers in Microbiology, 2026)
IntroductionHexamine and its by-products (formaldehyde and ammonia) are classified as organic pollutants. Formaldehyde has antibacterial properties, while increased ammonia levels contribute to eutrophication, both of which disrupts microbial communities in aquatic ecosystems. Hexamine is considered a common pollutant released from various industries.MethodsCulture based analysis in enriched medium resulted in development of bacterial consortium using environmental isolates.ResultsA consortium, containing six pure bacterial isolates {SRCHD03 & SRCHD04 (Brevundimonas diminuta), SRCHD05 & SRCHD07 (Brucella pseudintermedia), SRCHD06 (Ochrobactrum sp.), and SRCHD02 (Micrococcus luteus)} showed the ability to remove 1.26 g/kg hexamine associated with 0.87 g/kg of formaldehyde and 185.26 g/kg of Chemical Oxygen Demand (COD) at 96 hours of incubation under immobilized condition after 5.25 Gray of 60Co γ irradiations, starting from an initial concentration of 50 mg/L hexamine and 13367 mg/L COD, hence reporting the first radio tolerant consortium for hexamine removal.ConclusionInvolvement of Brucella pseudintermedia in hexamine and formaldehyde removal is being reported for the first time. The radio tolerant consortium in biofilm-based system showed enhanced hexamine, formaldehyde and COD removal efficiency compared to its suspended counterpart. This is a potential microbial formulation for the removal of hexamine and formaldehyde from stimulated wastewater.